Designing REACTION Media of Reading Skills for Islamic Senior High School - Bahtiar, Yuyun (Universitas KH. A. Wahab Hasbullah, 2022)
This researcher aimed to design media for reading skill for Islamic Senior High School. The research procedure uses research and development by using ADDIE’S method. ADDIE’S method has five steps. They are analysis, design, development, and implementation. This learning media in this research was designing REACTION (Reading Easy Application) media of reading skills for Islamic Senior High School. Sampling using product validation techniques with media experts, Material experts. Based on the results of validations and trials on multimedia using Hyperlink products, it can be reported validation of the material shows a percentage of 76 % which mean the media into good category. Based on the media validation shows a percentage of 72 % which mean the media into good category. Based on the tried out or implantation with students, the researcher got 88,28% of its mean include to the category of strongly agree. It can be concluded that the use of media-based Hyperlinks was valid and effective when implemented in English language learning in the classroom.